Peran Balai Latihan Kerja dalam Upaya Mengurangi Pengangguran: Studi pada UPTD BLK Kota Metro - Mirnawati, Mirnawati; Widodo, Wahyu; Setioko, Sigit; Maizayanti, Maizayanti (Tapis: Jurnal Penelitian Ilmiah, 2022)
The government has made various efforts to overcome the unemployment problem, one of them is through the UPTD BLK which is under the auspices of the Department of Labor (Disnaker). Efforts were being made to provide competency-based job training for the entire community in accordance with predetermined criteria. This study aimed to determine and analyze the role of UPTD BLK in providing job training to overcome unemployment in Metro City. This research employed a descriptive qualitative method by collecting data from interviews, documentation, and field observations. The results showed that there were three roles performed by UPTD BLK in alleviating unemployment, namely; 1) Active role by socializing training packages, providing training directly, evaluating by performing competency tests; 2) The role of participation by collaborating with related institutions that are willing to provide training; 3) Passive role in cooperation with third parties.